Public value road infrastructure maintenance - Rifai, Ifan; Hernanda, Willi Pranata; Hidayat, Moh Taufik; Heryanto, Yanto (International Journal Labs, 2024)
This research aims to understand the public value of road infrastructure maintenance in Cirebon City. This research is of a quantitative descriptive type. The findings of the study show (1) that the maintenance of road infrastructure in Cirebon City has been effectively implemented. The community's assessment of road maintenance in Cirebon City based on their answers, views, knowledge, and attitudes shows satisfaction. (2) Public value is the government's public value to the community in serving the community correctly and being satisfied with the service system from the government, getting the quality that customers or consumers want is satisfied with what they want. How can the community assess the services provided. (3) The highest average value of the public value is indicator 10, which is related to